2007
DOI: 10.1021/jp067383t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Determination of the Standard Reduction Potentials of Pheophytin-ainN,N-Dimethyl Formamide and Membrane

Abstract: A physicochemical interpretation of a recently formulated temperature-dependent, steady-state rate expression for the production of glucose equivalent in C(4) plants is given here. We show that the rate equation is applicable to a wide range of C(4) plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Firstly, we consider the values computed in the absence of a proton source. 29 In agreement with the experimental studies, addition of the first electron requires a strongly cathodic potential. The computed E RED values are somewhat different for the two solvents, with reduction being easier in CH 3 CN.…”
Section: Calculation Of Reduction Potentialssupporting
confidence: 85%
“…Firstly, we consider the values computed in the absence of a proton source. 29 In agreement with the experimental studies, addition of the first electron requires a strongly cathodic potential. The computed E RED values are somewhat different for the two solvents, with reduction being easier in CH 3 CN.…”
Section: Calculation Of Reduction Potentialssupporting
confidence: 85%
“…11,27,28,[69][70][71][72][73][74] In particular, for larger and complex biomolecules, calculation of absolute redox potentials are very successful using hybrid quantum mechanical and molecular mechanical (QM/MM) methods such as SCC-DFTB 11,27,28 and ONIOM calculation methods. 65,66,[75][76][77][78] The latter method has been used by Datta et al in a series of calculations to determine the absolute redox potentials of a number of biomolecules 61,65,66 while SCC-DFTB has recently been used for similar studies on various flavoenzymes. 11,27,28 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…For further discussion of the use of explicit-solvent simulations to compute reduction potentials, we refer readers to the relevant primary literature. 261,[266][267][268][269][270][271][272][273][274] The free energy problem in regard to MC and MD simulations is reviewed elsewhere. 262,275 Standard liquid-phase computer simulations usually utilize either a canonical ensemble, also called an NVT ensemble, 276,277 in which the number of particles (N), volume (V) and temperature (T) are conserved, or an isothermal-isobaric ensemble, also called an NPT ensemble, in which the pressure (P) rather than the volume is fixed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…450 The authors demonstrated that the method could be an efficient approach to free energy simulations of complex electron transfer reactions. 450 Several other enzymatic redox reactions have also been studied recently using the tools of computational electrochemistry, in particular for the following enzymes: photosystem II, 270,[451][452][453] ribonuclease reductase, 454,455 rubredoxin, 456 green fluorescent protein, 457,458 adenosine-5 0 -phosphosulfate reductase, 459 methyltransferases, 460 monoamine oxidase B, 461 and methionine synthase. 462 Billiet et al 463 have studied the thermodynamics of thiol sulfenylation in the sulfenic acid-forming protein human Prx.…”
Section: Applicationsmentioning
confidence: 99%